Serotonin signaling through lipid membranes - Kalinichenko, Liubov; Kornhuber, Johannes; Sinning, Steffen; Haase, Jana; Müller, Christian P. (ACS chemical neuroscience, 2024)
Serotonin (5-HT) is a vital modulatory neurotransmitter responsible for regulating most behaviors in the brain. An inefficient 5-HT synaptic function is often linked to various mental disorders. Primarily, membrane proteins controlling the expression and activity of 5-HT synthesis, storage, release, receptor activation, and inactivation are critical to 5-HT signaling in synaptic and extra-synaptic sites. Moreover, these signals represent information transmission across membranes. Although the lipid membrane environment is often viewed as fairly stable, emerging research suggests significant functional lipid-protein interactions with many synaptic 5-HT proteins. These protein-lipid interactions extend to almost all the primary lipid classes that form the plasma membrane. Collectively, these lipid classes and lipid-protein interactions affect 5-HT synaptic efficacy at the synapse. The highly dynamic lipid composition of synaptic membranes suggests that these lipids and their interactions with proteins may contribute to the plasticity of the 5-HT synapse. Therefore, this broader protein-lipid model of the 5-HT synapse necessitates a reconsideration of 5-HT’s role in various associated mental disorders.
Online veröffentlicht: 18. März 2024
Gesehen am 21.08.2024